Keberkesanan kendiri dan kerisauan di kalangan pelajar pendidikan tinggi: Tinjauan terhadap satu kursus teras universiti - Yusoff, Nuraini; Hashim, Jahara; Yaakub, Noran Fauziah; Awang Hashim, Rosna; Wan Chek, Noor Allam (Pusat Penyelidikan dan Perundingan, 2000)
A total of 940 students who are taking ‘introduction to Writing’ (in Malay) course in semester May 1998/99, were involved in this study. The questionnaire was administered to elicit answers to the following research objectives: 1. To identify the students self-efficacy and anxiety towards the Malay language; 2. To identify the factors involved in influencing the students’ self-efficacy and anxiety; and 3. To explain students’ self-efficacy and anxiety towards Malay language based on sex, early education and university entry-level qualification. The findings from this study show the influence of psychological factors on students and the teachings and learning implications at school and university level.